Key research questions of global importance for cetacean conservation - Parsons, E.; Baulch, S.; Bechshoft, T.; Bellazzi, G.; Bouchet, P.; Cosentino, A.; Godard-Codding, C.; Gulland, F.; Hoffmann-Kuhnt, M.; Hoyt, E.; Livermore, S.; MacLeod, C.; et al. (Inter-Research, 2015)
Limited resources and increasing environmental concerns have prompted calls to identify the critical questions that most need to be answered to advance conservation, thereby providing an agenda for scientific research priorities. Cetaceans are often keystone indicator species but also high profile, charismatic flagship taxa that capture public and media attention as well as political interest. A dedicated workshop was held at the conference of the Society for Marine Mammalogy (December 2013, New Zealand) to identify where lack of data was hindering cetacean conservation and which questions need to be addressed most urgently. This paper summarizes 15 themes and component questions prioritized during the workshop. We hope this list will encourage cetacean conservation-orientated research and help agencies and policy makers to prioritize funding and future activities. This will ultimately remove some of the current obstacles to science-based cetacean conservation.